N. brasiliensis infection is comparable between BALB/c and IL-4Rα−/lox mice. - Saskia Schmidt (109610) (2025)
Five mice per group were infected with 750 N. brasiliensis L3 larvae. Faeces were collected from day 5 to 10 post infection (PI) and egg production was calculated using the modified McMaster technique (A). At days 7 and 10 PI the worm burden in the small intestine was assessed (B). Intestinal goblet cell hyperplasia was assessed by determining the total number of PAS-positive goblet cells per 5 villi in histological sections of the small intestine at day 7 and 10 PI (C). Total IgE production in the serum was measured by ELISA at day 7 and 10 PI (D). Comparison of the response of infected BALB/c and IL-4Rα−/lox mice to acetylcholine is also shown for day 7 p.i. The data represents one (A-D) and two (E) independent experiment with n = 5 per group and mean values + SEM. ND, not detected. Unpaired two-tailed Student t test, ns = not significant. (TIF)